Effects of biotic/abiotic factors on the seedling regeneration of Dacrydium pectinatum formations in tropical montane forests on Hainan Island, China - Haodong Liu; Qiao Chen; Yongfu Chen; Zhiyang Xu; Yunchuan Dai; Yang Liu; Yi Jiang; Xi Peng; Huayu Li; Juan Wang; Hua Liu (Global Ecology and Conservation, 2020)
Exploring natural regeneration facilitates a better understanding of the mechanisms of community assembly and biodiversity formation. However, convincing data on tree regeneration in threatened tropical plant communities are lacking. Dacrydium pectinatum is a constructive and endangered species in tropical montane forests of Hainan Island. This study aims to identify the seedling regeneration patterns of D. pectinatum formation and their key drivers. A total of 204 seedling plots were investigated in the northwest (Bawangling, 90 plots), southwest (Jianfengling, 90 plots) and southeast (Diaoluoshan, 24 plots) of Hainan Island. We examined the variations in the seedling/adult composition, density and richness along local scales and elevation gradients and analyzed the relationships between biotic/abiotic variables and seedling regeneration. The seedling distribution pattern changed with environmental gradients, and the seedling density and richness decreased from low to high latitudes and from low to high elevations. Additionally, the adult density and total base area also showed consistent trends. At the community and species levels, the biotic neighborhood variables had a primary impact on the seedling density and richness. Multiple environmental factors (such as the canopy density, elevation, slope, soil organic matter, and soil total nitrogen) also showed significant correlations with the seedling density and richness. Our study supports conspecific negative density dependence and niche filtering as the general mechanisms of natural regeneration of D. pectinatum formations. Both biotic and abiotic factors might affect the survival and growth of seedlings, and their relative importance varies with environmental gradients and species. We conclude that enclosing forests with moderate stand densities in low-elevation areas to reduce human interference will help optimize the community structure. However, for high-elevation areas and high-density forests, appropriate thinning, manual regeneration and open gaps are needed to improve the light environment and soil nutrients, thereby promoting the natural regeneration of D. pectinatum formations.